Surface modification effect on the repair bond strength of hybrid and non-hybrid ceramics - Naeeme Naderi; Sara Majidinia; Mohammad Javad Moghaddas; Zahra Shooshtari; Melika Hoseinzadeh (BMC Oral Health)
Abstract Background This study investigated the appropriate surface treatment protocols for repairing various hybrid and non-hybrid ceramics. Methods Ceramic samples with a thickness of 2 mm were prepared from two resin-hybrid CAD/CAM blocks (Vita Enamic (hybrid-VE) and Lava Ultimate (hybrid-LU)) and two non-hybrid ceramics (VITABLOCS Mark II (non-hybrid-VM) and zirconia). The samples underwent 10,000 thermocycles. Their surfaces were then subjected to the following treatments before silanization and repair with resin composite using Tygon tubes with 1 mm diameter (n = 12): (1) no surface treatment, (2) grinding with silicon carbide, (3) sandblasting, and (4) etching with 9% hydrofluoric acid (HF). Then, ceramics were repaired using a universal adhesive agent (Clearfill Universal Bond; Kuraray, Tokyo, Japan) and composite resin. The microshear bond strength (µSBS) was measured and compared among the groups using two-way ANOVA and Tukey tests (α = 0.05). Results The type of ceramic and the surface treatment significantly influenced the repair µSBS (P < 0.05). The highest µSBS values for hybrid-VE, hybrid-LU, and non-hybrid-VM were respectively associated with surface preparation using silicon carbide grinding, sandblasting, and 9% HF etching (P < 0.05). For zirconia ceramics, the µSBS value was highest when treated with sandblasting, though this difference was not statistically significant. When no surface treatment was applied, or the samples were sandblasted, hybrid-LU and non-hybrid-zirconia showed the highest µSBS values (P < 0.05). When the surface was etched with 9% HF or ground with silicon carbide paper, hybrid-VE, and non-hybrid-VM demonstrated the lowest repair µSBS values, respectively (P < 0.05). Conclusion The optimal surface treatments for repairing hybrid-VE, hybrid-LU, and non-hybrid-VM ceramics were silicon carbide grinding, sandblasting, and 9% HF etching, respectively. However, surface treatments did not significantly affect the performance of zirconia ceramics.